2015
DOI: 10.1016/j.apsusc.2015.08.251
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale modeling of phase explosion in high fluence nanosecond laser ablation and clarification of ablation depth prediction criterion

Abstract: a b s t r a c tWhen phase explosion occurs, accurate prediction of the ablation behavior in the high energy nanosecond laser ablation process still remains a difficult challenge. In this paper, nanosecond laser ablation of aluminum and copper with phase explosion is investigated through a multi-scale model and experimental verification. The melt ejection behavior during phase explosion is successfully predicted by combined molecular dynamics (MD) and smoothed particle hydrodynamics (SPH) simulations and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…The authors of this manuscript previously suggested a thermal model of DLIP for metallic substrates [35]. Cao and Shin predicted the particle motion due to phase explosion during high fluence laser ablation of metals by SPH [36]. Further, Alshaer et al used SPH to simulate the thermal ablation of aluminium at elevated fluences, particularly the ejection of particles by the recoil pressure [37].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this manuscript previously suggested a thermal model of DLIP for metallic substrates [35]. Cao and Shin predicted the particle motion due to phase explosion during high fluence laser ablation of metals by SPH [36]. Further, Alshaer et al used SPH to simulate the thermal ablation of aluminium at elevated fluences, particularly the ejection of particles by the recoil pressure [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, complete suppression of the laser-induced particle ejection from the target was difficult. The mechanisms of phase explosion and/or hydrodynamic liquid phase spraying may cause the formation of particles when intensities of the pulsed laser ablation are varied from higher to relatively low [54][55][56].…”
Section: The Structure and Composition Of Mos X Filmsmentioning
confidence: 99%
“…When the molten material temperature approaches 0.8-0.9 T c , the stability of the superheated liquid becomes drastically more sensitive on density fluctuations and the homogeneous bubble nucleation rate. The process that the superheated liquid seeks for the equilibrium would lead to its return to the binodal through phase explosion [35][36][37][38]49,50]. Based on the kinetic theory, the phase explosion would be triggered by the spontaneous expansion of bubbles when they reach a critical radius, r c .…”
Section: Laser-materials Interaction Analysismentioning
confidence: 99%